2021
DOI: 10.1098/rspb.2020.3164
|View full text |Cite
|
Sign up to set email alerts
|

Habitat loss on the breeding grounds is a major contributor to population declines in a long-distance migratory songbird

Abstract: Many migratory species are declining and for most, the proximate causes of their declines remain unknown. For many long-distance Neotropical migratory songbirds, it is assumed that habitat loss on breeding or non-breeding grounds is a primary driver of population declines. We integrated data collected from tracking technology, community science and remote sensing data to quantify migratory connectivity (MC), population trends and habitat loss. We quantified the correlation between forest change throughout the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…Furthermore, populations of many species of birds are declining at the trailing edge of their breeding ranges in the southern Appalachians (Sauer et al, 2017 ), despite wintering in broadly different areas of the Neotropics. Taken together, our results strongly support the hypothesis that climate change on the breeding grounds contributes to local population declines in black‐throated blue warblers, but further research is needed to determine how climate change on the breeding grounds interacts with threats encountered during other seasons to shape population dynamics throughout the annual cycle (e.g., Hallworth et al, 2021 ; Rushing et al, 2017 ; Sillett et al, 2000 ). Understanding the drivers of range contractions of migratory birds in montane regions is critically important.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, populations of many species of birds are declining at the trailing edge of their breeding ranges in the southern Appalachians (Sauer et al, 2017 ), despite wintering in broadly different areas of the Neotropics. Taken together, our results strongly support the hypothesis that climate change on the breeding grounds contributes to local population declines in black‐throated blue warblers, but further research is needed to determine how climate change on the breeding grounds interacts with threats encountered during other seasons to shape population dynamics throughout the annual cycle (e.g., Hallworth et al, 2021 ; Rushing et al, 2017 ; Sillett et al, 2000 ). Understanding the drivers of range contractions of migratory birds in montane regions is critically important.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, one can conclude that neotropical migrants are an important component in bird diversity responding to agricultural land use practices. These may not be surprising in view that Hallworth et al (2021) provide evidence that at least for some neotropical migrants it is habitat loss in the breeding grounds that matter for population declines.…”
Section: T a B L E 3 Main Regression Resultsmentioning
confidence: 99%
“…This study systematically revealed the spatial-temporal patterns of the spotted seal population in the Yellow Sea ecoregion based on tracking of individuals and the climatic conditions of the sites where they were monitored. Within the life history, habitat loss during the breeding or wintering season is an important driver of population decline in migratory species (Hobson & Wassenaar 1996;Flockhart et al 2015;Hallworth et al 2021). December, January, and February comprised both the breeding and wintering seasons for spotted seals (Jia & Jian 2015;Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2015; Hallworth et al. 2021). December, January, and February comprised both the breeding and wintering seasons for spotted seals (Jia & Jian 2015; Fig.…”
Section: Discussionmentioning
confidence: 99%